The Information Content of Municipal Spending Rate Data - Apostolou, Nicholas G.; Giroux, Gary A.; Welker, Robert B. (Journal of Accounting Research, 1985)
Municipal bonds, Spending rate, Riskiness of Municipal bonds, Information content